PENGARUH FIRM SIZE, LEVERAGE DAN PROFITABILITY TERHADAP ECONOMIC VALUE ADDED (EVA) PADA EMITEN MANUFAKTUR DI BURSA EFEK INDONESIA - Rahma, Maharani (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2018)
The purpose of this research is to analyze the effect of the Firm Size, Leverage and Profitability Tto Economic Value Added on emiten manufactur in Indonesia Stock Exchange. The selected independent variables in this study are Total Asset, Debt to Equity Ratio (DER) and Return on Equity (ROE) and the dependent varable is Economic Value Added (EVA). This research was conducted on manufactur listed issuers in Indonesia Stock Exchange in 2010-2014 period. Research carried out by using 59 sampels based on stratefied random sampling method. Panel Data Regression Models with Generalized Least Squares (GLS) method is used to data analysis and hipothesis testing. The results of this research and hypothesis testing indicate that: (1) Partially,Total Assets,ROE have a possitively relationships with significantly affect to the EVA and DER have a possitvely relationships with not significantly affect to the EVA.(2) Total Asset, DER and Profitability simultaneously have possitively relationship with significantly affect to the EVA. (3) model in this study showed a weak pattern relationships between the dependent variable with the independent variables. Keywords : Firm Size, Leverage, Profitability, Economic Value Added, panel data